Philosophy of Science in Islamic Thought Perspective - Marlian Arif Nasution (Program Doktor Akidah dan Filsafat Islam, 2020)
Tracing a starting point that is very important from the traditional Islamic sciences, modern Western science was developed such that it adopts a philosophical footing. Unlike modern Islamic science, the philosophical footing is to be distinguished from the philosophical foundation of Islamic science. Indeed, Islamic science main concern is closely related to the basic philosophy of science issues is growing and is recognized today, including science paradigms and methodologies developed in the modern world that is more influenced by the thinking paradigm of the modern secular Western philosophy. This implies bias in epistemology and axiology between science and moral paradigm developed in Islam. In the practical level of science that was developed to be dried from a religious touch, these conditions afflict various disciplines of knowledge that Muslims studied. Therefore, Muslims increasingly need to differentiate between Islam and science that is not Islamic. Today, not many intellectual issues are more important to the contemporary Islamic world beyond the relationship between Islam and modern science.